CHARACTERISTICS OF THE FUNDAMENTALS OF LATIN LANGUAGE TERMINOLOGY - Yusupova Manzura Kurbanovna (University Research Base, 2024)
Latin is considered the root language from which many modern European languages originate. Due to its widespread historical use, Latin terminology remains prevalent in many academic and scientific fields today. The retention of Latin terms stems from certain intrinsic characteristics that have allowed its terminology to endure over time. This article will explore some of the key fundamentals of Latin language terminology that have contributed to its persistence as the foundation of vocabulary in numerous domains.